Progression Measurement of Visual Field Loss in Medically Controlled Primary Open-Angle Glaucoma (POAG): Visual field loss in POAG - Zehra, Maham; Anwar, Mohd Shakaib; Yousafzai, Erum; Akhter, Waseem; Ain, Qura -Tul-; Shafique, Maeirah (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine mean visual field parameters loss (Mean deviation and Pattern standard deviation) and frequency of glaucoma hemifield test to evaluate optic nerve damage progression in medically well-controlled primary open-angle glaucoma POAG through standard automated perimetry. Study Design: Prospective longitudinal study. Place and Duration of Study: Department of Ophthalmology, Rawal Institute of Health Sciences, Islamabad Pajistan, from Sep 2019 to March 2020. Methodology: Fifty-four patients were inlcuded. Visual field parameters included the Glaucoma hemifield test, Mean deviation, and Pattern standard deviation. The visual field loss progression was evaluated through Humphry analyzer 30-2. Follow-up was done on the first day of the presentation, then after three and six months. Results: We found an increase in intraocular pressure (14.59±1.3 vs 15.87±2.1, p<0.001, 16.44±2.4, p<0.001, Mean deviation (- 9.381±6.5 vs -10.905±8.9, p=0.05, -11.034±9.9=0.05) and Pattern standard deviation (6.158±4.1 vs 6.133±4.3, p<0.001, 6.502±4.2, p<0.001) at 1st day, 3-monthS and 6-monthS respectively. Glaucoma hemifield test was outside normal in 39(72.2%), 45(83.3%), 50(92.6%) patients, borderline in 5(9.3%), 4(7.4%), 2(3.7%) patients, within normal in 6(11.1%), 3(5.6%), 1(1.9%) patient at 1stday, 3-months and 6-months respectively. Conclusion: Primary open-angle glaucoma patients with medically controlled conditions show an increasing trend in visual field parameters, including mean standard deviation, pattern standard deviation and glaucoma hemifield test measurement with the progression of the disease